2009
DOI: 10.1007/s11357-008-9084-x
|View full text |Cite
|
Sign up to set email alerts
|

Thymopoiesis in elderly human is associated with systemic inflammatory status

Abstract: Immunosenescence studies of age-related immune system damage focused on clinical lymphopenic situations or androgenic blockade have revealed new insights about adult human immune reconstitution. However, as far as we know, the extent of lymphopoiesis in the thymus of elderly humans remains unclear. To this effect, we have analyzed 65 adult human thymuses (from 36 to 81 years; median age 68.6 years) obtained from patients who underwent cardiac surgery. Our results show a correlation between CD4 + CD8 + double-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 39 publications
3
40
1
Order By: Relevance
“…1d). As previously showed (Ferrando-Martinez et al 2009) elderly individuals show a wide range of thymic functionality that directly affects the naive T cell pool. Percentages of DP thymocytes were analyzed as thymic function gold standard and a representative flow cytometry example is shown as Fig.…”
Section: Analysis Of Naive T Cells Homeostatic Parametersmentioning
confidence: 71%
See 2 more Smart Citations
“…1d). As previously showed (Ferrando-Martinez et al 2009) elderly individuals show a wide range of thymic functionality that directly affects the naive T cell pool. Percentages of DP thymocytes were analyzed as thymic function gold standard and a representative flow cytometry example is shown as Fig.…”
Section: Analysis Of Naive T Cells Homeostatic Parametersmentioning
confidence: 71%
“…The slight lymphopenia shown in elderly people reduces self-MHC contacts, needed for naive homeostasis (Takada and Jameson, 2009). Besides, IL-7 availability is maintained, or even increased (Ferrando-Martinez et al 2009). Since naive T cell compartment is independently regulated, less MHC contacts, and stronger IL-7-derived survival signals (described as sense of a naive immune space) allow naive T cells to proliferate in a similar way as naive T cells transferred to lymphopenic hosts do (Ernst et al 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results show that thymic function-related deterioration of the adaptive response and systemic inflammation act independently by affecting human survival. Despite the well-described age-related atrophy (Chiodi 1940;Henry 1967), we have previously shown that thymic function in elderly humans is widely heterogenic, and the thymus that remains functional in elderly individuals has a direct role in the peripheral T cell pool maintenance (Ferrando-Martínez et al 2009). In addition, a higher elderly thymic function correlates with younger and better-preserved peripheral naive T cell subset (Ferrando-Martínez et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Thymopoietic degree is widely heterogeneous among individuals (Figure 3). In addition, thymic function in elderly people has an active role in the peripheral immune system rejuvenation (Ferrando-Martínez et al, 2009). Higher thymic function in elderly human is associated with a better preservation of the immune system.…”
Section: Thymic Failure During Adulthood and Elderlymentioning
confidence: 99%